A case of eosinophilic granulomatosis with polyangiitis (churg-strauss, EGPA) presenting with relapsed mononeuritis multiplex - Abdullah, Hilmi; MM, Ainon (The Faculty of Medicine, International Islamic University Malaysia, 2014)
We report a case of eosinophilic granulomatosis with polyangiitis (EGPA), a rare multisystem disorder characterized by difficult-to-control asthma, hypereosinophilia and polyneuropathy. We also discuss the Five Factor Score (FFS) risk stratification strategy, which is used to quantitate the extent of the disease and guide treatment strategy.